2011
DOI: 10.1371/journal.pone.0018440
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use in Patients with Fibromyalgia: Effect on Symptoms Relief and Health-Related Quality of Life

Abstract: BackgroundThe aim of this study was to describe the patterns of cannabis use and the associated benefits reported by patients with fibromyalgia (FM) who were consumers of this drug. In addition, the quality of life of FM patients who consumed cannabis was compared with FM subjects who were not cannabis users.MethodsInformation on medicinal cannabis use was recorded on a specific questionnaire as well as perceived benefits of cannabis on a range of symptoms using standard 100-mm visual analogue scales (VAS). Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 14 publications
1
86
1
2
Order By: Relevance
“…Comments offered by respondents to the current survey are consistent with findings from a previous survey and qualitative studies on medicinal cannabis use. Cannabis users have consistently reported anecdotal evidence for symptom improvement, although the proportion reporting benefit has varied widely . The only previous Australian survey ( n = 128) found that around a quarter of medicinal cannabis users across a variety of health conditions used it for appetite loss, and nearly all reported ‘great’ or ‘good’ relief .…”
Section: Discussionmentioning
confidence: 99%
“…Comments offered by respondents to the current survey are consistent with findings from a previous survey and qualitative studies on medicinal cannabis use. Cannabis users have consistently reported anecdotal evidence for symptom improvement, although the proportion reporting benefit has varied widely . The only previous Australian survey ( n = 128) found that around a quarter of medicinal cannabis users across a variety of health conditions used it for appetite loss, and nearly all reported ‘great’ or ‘good’ relief .…”
Section: Discussionmentioning
confidence: 99%
“…After cannabis consumption, the cannabis‐users group exhibited a reduction in pain and stiffness as well as an increase in relaxation, somnolence, and feeling well, and achieved scores of mental health component in Short Form Health Survey‐36. However, no significant improvements were found in Short Form Health Survey‐36 other components as well as in the Fibromyalgia Impact Questionnaire and the Pittsburgh Sleep Quality Index …”
Section: Cannabis and Autoimmune Diseasesmentioning
confidence: 91%
“…However, the high concentration of CBG (16 mg/g), a phytocannabinoid known to be an α‐2 adrenoreceptor and the serotonin 1A receptor (5‐ HT1A) agonist, and terpenoid myrcene (5 mg/g) in this formulation could explain the analgesic and myorelaxant effect recorded in most patients (75%). Also, the improvement of neurologic symptoms (improvement in mood and concentration) might be due to this selected formula containing Δ 9 ‐THC and CBD at the ratio of 22 : 1 that could mitigate the beta‐amyloid peptide (Aβ) level‐evoked neuroinflammatory and neurodegenerative responses . A recent study in vitro evidenced that low doses of Δ 9 ‐THC solution (100 μl at 2× concentrations in each well) added in mouse neuroblastoma cell line (N2a/AβPPswe cells) lowed the Aβ level, the total and phosphorylated GSK‐3β levels (protein kinase that has a key role in the pathogenesis of both sporadic and familial AD) .…”
Section: Discussionmentioning
confidence: 99%